Integrated strategies offer site-specific control of yellow starthistle - Joseph DiTomaso; Steven F. Enloe; Guy Kyser; Steve Orloff (California Agriculture, 2000)
Ongoing research projects integrate chemical, mechanical, cultural and biological techniques to control yellow starthistle, a prolific weed now infesting between 10 million and 15 million acres in California. With many options available to land managers, developing a long-term, strategic management plan most suitable to a specific area can be complicated. It requires careful consideration of the advantages and disadvantages of each option and how best to incorporate appropriate ones into an effective program. Management strategies include timely mowings, grazing, clover plantings, biological control insects, prescribed burning and selective applications of herbicides. In addition to new developments in the management of yellow starthistle, public awareness of invasive weed issues has translated into major legislative changes that should encourage and assist private and public landowners and managers to initiate long-term programs to prevent and manage invasive weeds, particularly yellow starthistle.